2019
DOI: 10.30880/ijie.2019.11.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Myoelectric Signal using Spectrogram Based Window Selection

Abstract: This paper presents a study of the classification of myoelectric signal using spectrogram with different window sizes. The electromyography (EMG) signals of 40 hand movement types are collected from 10 subjects through NinaPro database. By employing spectrogram, the EMG signals are represented in time-frequency representation. Ten features are extracted from spectrogram for performance evaluation. In this study, two classifiers namely support vector machine (SVM) and linear discriminate analysis (LDA) are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…While artificial neural networks have shown promising results in EMG signal classification [ 21 , 50 ], other machine learning algorithms, such as Support Vector Machine [ 51 , 52 ], K Nearest Neighbors [ 53 , 54 ], and Multilayer Perceptron [ 55 ], have also been successfully employed in this domain [ 56 ]. The choice of algorithm often depends on the specific requirements and characteristics of the classification task.…”
Section: Background and Related Workmentioning
confidence: 99%
“…While artificial neural networks have shown promising results in EMG signal classification [ 21 , 50 ], other machine learning algorithms, such as Support Vector Machine [ 51 , 52 ], K Nearest Neighbors [ 53 , 54 ], and Multilayer Perceptron [ 55 ], have also been successfully employed in this domain [ 56 ]. The choice of algorithm often depends on the specific requirements and characteristics of the classification task.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Several studies showed the usefulness of TD, especially in terms of its quickness, simplicity, and lack of any necessary transformation. [12]. The main disadvantage of the TD is that the features are produced by the signal's stationary nature.…”
Section: Step2 : Feature Extractionmentioning
confidence: 99%
“…Discrete Wavelet Transform (DWT) is one of the tools for analyzing and processing signals and images, allowing for efficient representation of information at different scales and frequencies. It has found applications in various fields, including vision and audio processing, data compression, and feature extraction [10]. For the identification process, the Neural network algorithm is used.…”
Section: Introductionmentioning
confidence: 99%